2020
DOI: 10.18488/journal.137.2020.41.26.40
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Behavioral Intention to Listen to IIUM.FM among Non-Listeners

Abstract: This study is part of a longitudinal study done on the audience reception of IIUM.FM, a campus radio the first study or phase 1 was done in 2011 and the second phase was done in 2016. This study specifically compares the non-listeners in Phase 1 (2011) and Phase 2 (2016) in terms of demographic characteristics, academic-related information and computer-related information. In addition, both internal and external factors that may intensify the listening to IIUM.FM are explored and so that the barriers and chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…This is supported by the respondent's answer to the question "I use herbal medicine because it's useful (beneficial)," with the overall percentage of respondents who responded agreeing at 88.56% of total respondents. This is in line with Mohamed, (2004), whose study reported that the consumer's intention in choosing herbal products is influenced by several factors and the attitude towards treatment is the main determinant of the tendency of the consumer's intention to consume herbal products.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This is supported by the respondent's answer to the question "I use herbal medicine because it's useful (beneficial)," with the overall percentage of respondents who responded agreeing at 88.56% of total respondents. This is in line with Mohamed, (2004), whose study reported that the consumer's intention in choosing herbal products is influenced by several factors and the attitude towards treatment is the main determinant of the tendency of the consumer's intention to consume herbal products.…”
Section: Discussionsupporting
confidence: 88%
“…Ajzen (1991) stated that a person's behavior depends on the desire to behave. The tendency of intention to behavior is influenced by attitudes towards behavior, subjective norms, and perceived behavioral control (Mohamed, 2004). Perceived behavioral control indicates that perceptions of ease and difficulty motivate a person to perform a certain behavior.…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
See 1 more Smart Citation